A Look at the Methodological Issues Involved in the Greek-Turkish Arms Race Hypothesis - Kollias, Christos (Études helléniques / Hellenic Studies, 2001)
Greece and Turkey are both members of the NATO Alliance, yet disputes and conflicts mar their bilateral relations. In the recent past, concomitant tensions and frictions have brought the two countries to the brink of war. Both countries allocate a substantial part of their national economy to defense. Even during the post bipolar period, their respective military expenditures have continued to grow in real terms at a time when other NATO members have been trimming their defense spending. The hypothesis of a Greek-Turkish arms race has been trimming their defense spending. The hypothesis of a Greek-Turkish arms race has been the subject of a number of empirical studies in the defense economics literature, but the issue of the empirical verification of such a race remains at best inconclusive. This paper addresses some methodological issues which hinder the empirical examination of the Greek-Turkish armaments race.